Do Environmental Costs Impact Financial Sustainability? An Emerging Market’s Perspective. - Thomas NYAHUNA; Mishelle DOORASAMY (International Journal of Environmental, Sustainability, and Social Science, 2023)
The importance of properly managing environmental costs cannot be underestimated. This paper investigated the relationship between environmental costs and financial performance of 45 cement and mining listed on the Johannesburg Stock Exchange from 2014 to 2021. Financial performance is measured by return on equity whilst environmental cost is proxied by carbon management costs, recycling costs and pollution prevention costs. Control variables such as growth, leverage, size and debt ratio are used in this study. The study applied a quantitative research approach using an ex-post facto research design. The researchers adopted a panel regression analysis. The result of the study indicates a negative and significant association between environmental costs and return on equity. It was concluded that environmental costs reduce profitability in form of return of equity of the sampled companies. This study has practical implications of motivating corporate managers to proactively manage environmental costs in order to improve corporate financial performance. Additionally, it helps to practically shape environmental policies that intend to augment environmental performance.